CO/CO2 Study of High Performance La0.3Sr0.7Fe0.7Cr0.3O3–δ Reversible SOFC Electrodes1. Issue 5 (21st September 2015) - Addo, P. K.; Molero‐Sanchez, B.; Chen, M.; Paulson, S.; Birss, V.; Christiansen, Niels; Hagen, Anke; Bele, Petra; Bucheli, Olivier
Abstract In this study, we demonstrate that the La0.3Sr0.7Fe0.7Cr0.3O3–δ (LSFCr) perovskite, examined here as a CO/CO2 fuel electrode material intended for symmetrical, reversible solid oxide fuel cell (RSOFC) applications, is both high performing and stable towards CO2 electrolysis (SOEC mode) and the oxidation of CO (SOFC mode). To demonstrate this, symmetrical LSFCr/GDC/YSZ/GDC/LSFCr cells were evaluated electrochemically by using both DC (cyclic voltammetry (CV) and galvanostatic) and AC (impedance) techniques. The cells were tested at 800 °C using either 90% CO2:10% CO or 70% CO2:30% CO at the fuel electrode and air flowing to the O2 electrode. From the open circuit impedance data, the polarization resistance, measured at 800 °C in a 90% CO2:10% CO and 70% CO2:30% CO gas composition, was 1.3 Ω cm2 and 0.9 Ω cm2, respectively. Both the CV and polarized impedance data showed that the cell performance is higher during the electrolysis of CO2 than for the oxidation of CO. Furthermore, the cell showed a very stable activity during CO2 electrolysis, with a degradation rate of only 0.057 mV h−1 after ca. 135 h of galvanostatic testing at –100 mA cm−2 in 90% CO2:10% CO at 800 °C.